Growth factor sequestration and enzyme-mediated release from genipin-crosslinked gelatin microspheres. Issue 16 (2nd November 2017) - Turner, Paul A.; Thiele, Jeffrey S.; Stegemann, Jan P.
Abstract: Controlled release of growth factors allows the efficient, localized, and temporally-optimized delivery of bioactive molecules to potentiate natural physiological processes. This concept has been applied to treatments for pathological states, including chronic degeneration, wound healing, and tissue regeneration. Peptide microspheres are particularly suited for this application because of their low cost, ease of manufacture, and interaction with natural remodeling processes active during healing. The present study characterizes gelatin microspheres for the entrapment and delivery of growth factors, with a focus on tailored protein affinity, loading capacity, and degradation-mediated release. Genipin crosslinking in PBS and CHES buffers produced average microsphere sizes ranging from 15 to 30 microns with population distributions ranging from about 15 to 60 microns. Microsphere formulations were chosen based on properties important for controlled transient and spatial delivery, including size, consistency, and stability. The microsphere charge affinity was found to be dependent on gelatin type, with type A (GelA) carriers consistently having a lower negative charge than equivalent type B (GelB) carriers. A higher degree of crosslinking, representative of primary amine consumption, resulted in a greater negative net charge. Gelatin type was found to be the strongest determinant of degradation, with GelA carriers degrading at higher rates versus similarly crosslinked GelB carriers. Growth factor release was shown to depend upon microsphere degradation by proteolytic enzymes, while microspheres in inert buffers showed long-term retention of growth factors. These studies illuminate fabrication and processing parameters that can be used to control spatial and temporal release of growth factors from gelatin-based microspheres.